Association between smoking and glycemic control in men with newly diagnosed type 2 diabetes: a retrospective matched cohort study - Hon-Ke Sia (Annals of Medicine, 2022)
Background Longitudinal data on the association between smoking and glycemic control in men with newly diagnosed type 2 diabetes (T2DM) is scarce. Therefore, this study aimed to examine the extent of the association between smoking and glycemic control in this population.Methods The retrospective cohort study identified 3044 eligible men with T2DM in a medical centre in Taiwan between 2002 and 2017. Smokers (n = 757) were matched 1:1 with non-smokers using propensity score-matching. All of them were followed for one year. Glycated haemoglobin (HbA1c) levels were measured at 0, 3, 6, 9, and 12 months after enrolment. Generalised estimating equations were used to assess smoking status-by-time interaction to determine the difference in HbA1c reduction between the two cohorts. All analyses were performed in 2020.Results The estimated maximal difference in HbA1c reduction between smokers and non-smokers was 0.33% (95% CI, 0.05–0.62%) at 3 months of follow-up. For patients with body mass index (BMI) <25 kg/m2, the difference in HbA1c reduction between smokers and non-smokers was much larger (0.74%, 95% CI, 0.35–1.14%) than in those with a higher BMI.Conclusions Our findings show that smoking was independently associated with unfavourable glycemic control among men with newly diagnosed T2DM, and such a detrimental association could be stronger in men with a lower BMI.